2020
DOI: 10.26832/24566632.2020.0504023
|View full text |Cite
|
Sign up to set email alerts
|

Integrated pest management of fall armyworm infestations in maize fields in Nepal: A review

Abstract: Spodoptera frugiperda, commonly known as Fall Armyworm (FAW), is amongst the most terrifying pests of maize in Latin America, which unexpectedly appeared in Nepal in 2019 and spread expeditiously. Estimates of maize crop losses due to this pest are vital in order to compare the effect of these losses with the convenient of controlling FAW and suggest pertinent controlling technology and methods. Nepal is predominantly an agrarian nation thus, maize is grown substantially. However, climatic conditions of Nepal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…Hence, the alternative technique for the management of FAW should be environment-friendly and cost effective. It was reported that the integrated approach includes push-pull technology, use of botanical extracts, intercropping, natural enemies and parasitoids, utilizing locally available materials like sand, ash, sawdust, etc effectively reduces the incidence of FAW [6,7]. Keeping this in view, the present investigation has been carried out to find a management option that deliberates ecological values.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the alternative technique for the management of FAW should be environment-friendly and cost effective. It was reported that the integrated approach includes push-pull technology, use of botanical extracts, intercropping, natural enemies and parasitoids, utilizing locally available materials like sand, ash, sawdust, etc effectively reduces the incidence of FAW [6,7]. Keeping this in view, the present investigation has been carried out to find a management option that deliberates ecological values.…”
Section: Introductionmentioning
confidence: 99%
“…The integrated pest management (IPM) concept mainly focuses on the use of the natural enemy of the pest as a biological control method that is environmentally friendly and sustainable (Khatri et al, 2020). Natural enemies such as predatory arthropods and parasitic wasps play important role in managing arthropod pest populations (Hajek and Eilenberg, 2018) in agro-ecosystems (El-Wakeil and Volkmar, 2013;Ali et al, 2018).…”
Section: Dorji Et Al 2022 B Amentioning
confidence: 99%
“…Maize has diversified uses such as animal feeds, poultry feeds, and human consumption (such as Kharang, Tengma, cornmeal and flour) besides other uses (DAMC, 2019). Maize plants are sensitive to insect pest infestations despite their high genetic yield potential (Khatri et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The rapid global expansion of FAW in short period is because of its migratory behaviour, high dispersal capacity, significant flying ability and high fecundity (Khatri et al, 2020). Moreover, in Africa and Asia, the climatic conditions for fall armyworm are ideal, allowing it to develop many generations in a single season, resulting in the pest becoming endemic to this region.…”
Section: Faw In Indiamentioning
confidence: 99%